5S As a Form of Lean Manufacturing Implementation in the Perspective of Human Resources: A Case Study in Food SMEs - Made Iska Aprilia Wardhani; Tasnim Nikmatullah Realita (Yayasan Literasi Sains Indonesia, 2022)
The objectives of this research are to find out employees' understanding of lean manufacturing and 5S and how it is implemented. These research methods are a type of qualitative research using a case study approach which was carried out at food SMEs. data collection was carried out through a series of field observation procedures and interviews with employees and leaders. The results of the research show that employees' understanding of the company cannot be said to be good. This is indicated by the results of observations and interviews which present the fact that employees do not know exactly how 5S should be implemented and what are the benefits of being disciplined in carrying out company operations using 5S. the company has provided various supporting documents and facilities and infrastructure, but this was not accompanied by socialization and training procedures, resulting in not optimal implementation of the 5S. Lean manufacturing deployment was found to be restricted by the human resource aspect, which could not be realized.